Effect of the MyDéfi Smartphone Application on Binge Drinking Among University Students: Protocol of a Double‐Blind Multicenter Prospective National Randomized Controlled Trial Using Phosphatidylethanol as a Biomarker—The SMARTBINGE Trial - Camille André; Pierre Sauton; Méléna Dreinaza; Momar Diouf; Sandra Bodeau; Margaret Martinetti; Raphaël Trouillet; Clara deGroote; Jean‐Louis Nandrino; Adèle Alexandre; Farid Benzerouk; Fabien Gierski; et al. (International Journal of Methods in Psychiatric Research, 2025)
ABSTRACT Objective The purpose of this paper is to describe a study protocol of a clinical trial exploring the effectiveness of the new mobile application MyDéfi proposing personalized feedback, on both alcohol consumption and quality of life, as well as the blood alcohol exposure biomarker phosphatidylethanol, in university students displaying binge drinking behavior. Methods This prospective national multicentric randomized, two‐arm (1:1), double‐blind controlled trial will recruit 628 students (aged 18–25 years) with binge drinking behavior. Participants will be randomized in the “intervention” group (personalized feedback) or the “control” group (generic feedback) and will undergo four monthly visits. Monthly dried blood spot sample for measuring phosphatidylethanol concentration and online questionnaires will be collected. Our primary objective is to assess the reduction weekly standard drinks, through self‐report gathered via MyDéfi. Secondary objectives will evaluate the application's impact on the dosage of phosphatidylethanol blood concentration and on quality of life”. Results Recruitment started in March 2024 and will end in March 2026. Conclusion This study aims to determine the effectiveness of two versions of the same mobile application (generic vs. personalized feedback) on alcohol consumption in students displaying binge drinking behavior. The effectiveness of the application will be measured, with a secondary objective of quantifying phosphatidylethanol. Our study will open new perspectives on the use of digital interventions for students who do not actively seek treatment. Trial Registration Trial registration number (NCT06084832), the date of registration (10th October 2023) and when this was done (16th October 2023). https://clinicaltrials.gov/study/NCT06084832